Characterization of a mutant of Haemophilus influenzae type b lacking the P2 major outer membrane protein. - Cope, L D (1990)
An isogenic mutant of Haemophilus influenzae type b (Hib) lacking the ability to express the P2 major outer membrane (porin) protein was constructed and characterized in various model systems. Linker insertion mutagenesis of a cloned Hib DNA insert containing the P2 structural gene was used in conjunction with a genetic transformation system to obtain a transformant unreactive with a P2-specific monoclonal antibody. This transformant was shown to lack detectable P2 protein by both protein staining and immunoblot methods. The P2 mutant exhibited a generation time in complex broth medium that was significantly longer than that of the wild-type parent strain. The P2 mutant was also unable to produce detectable bacteremia in infant rats after intraperitoneal challenge, while the wild-type parent strain produced bacteremia in all animals challenged with this strain. Reintroduction of a wild-type copy of the P2 gene into this mutant yielded a transformant strain that had a generation time in vitro identical to that of the wild-type parent strain and that was also fully virulent in the infant rat model. These findings suggest that the ability to synthesize the P2 protein may be necessary but not sufficient for full expression of virulence by this pathogen.